Leiomyoma of the fallopian tube found during laparoscopic myomectomy: A case report and review of the literature - Cheng, Bing; Wang, Rui; Fu, Yaoqun; Fu, Xi (Frontiers in Surgery, 2023)
Leiomyoma of the fallopian tube is an extremely rare benign tumor of the fallopian tube. Because of the small number of cases, it is difficult to calculate their incidence. In this case report, we report a case of leiomyoma of the fallopian tube detected during laparoscopic myomectomy in a 31-year-old female with occasional pelvic pain. The patient was diagnosed with uterine leiomyoma based on a transvaginal ultrasound scan. She was operated and a 3*3 cm mass in the area of the isthmus of the left fallopian tube was observed. Three uterine leiomyomas and one leiomyoma of the fallopian tube were removed. Ultrasound at 6 months postoperatively showed no abnormality. Hysterosalpingo-contrast-sonography (HyCoSy) at 15 months postoperatively showed bilateral fallopian tubes were unobstructed. For those patients with fertility requirements, some fertility-preserving techniques can be used to allow complete resection of the leiomyoma and avoid tubal damage.